Hot Carriers: Plasmonic Au/TiO2‐Dumbbell‐On‐Film Nanocavities for High‐Efficiency Hot‐Carrier Generation and Extraction (Adv. Funct. Mater. 34/2018). (20th August 2018) - Ho, Kwun Hei Willis; Shang, Aixue; Shi, Fenghua; Lo, Tsz Wing; Yeung, Pui Hong; Yu, Yat Sing; Zhang, Xuming; Wong, Kwok‐yin; Lei, Dang Yuan
Abstract : Plasmonics sensitization enables semiconductors absorbing sub‐bandgap photons through the generation of hot carriers in metallic nanostructures and subsequent transfer to adjacent semiconductors. To that end, Dang Yuan Lei and co‐workers present a Au@TiO2 dumbbell‐on‐film nanocavity in article number1800383 . Non‐radiative decay of the localized surface plasmons in the dumbbell and the inter‐band transitions in the Au film allow for dual‐channel hot‐carrier generation with the hot electrons from both channels being transferred to TiO2 for visible‐light‐driven photocatalysis.